Housing as a Social Determinant of Health in Singapore and Its Association with Readmission Risk and Increased Utilization of Hospital Services - Low, Lian Leng; Wah, Win; Ng, Matthew Joo; Tan, Shu Yun; Liu, Nan; Lee, Kheng Hock (Frontiers in Public Health, 2016)
Abstract Background: Residence in public rental housing is an area-level measure of socioeconomic status but its impact as a social determinant of health in Singapore has not been studied. We therefore aimed to examine the association of public rental housing with readmission risk and increased utilization of hospital services in Singapore. Methods: We conducted a retrospective cohort study using retrospective 2014 data from Singapore General Hospital’s electronic health records. Variables known to affect readmission risk and healthcare utilization were identified a-priori and in clude patient demographics, comorbidities, healthcare utilization in the preceding one year and clinical variables from the index admission in 2014. Multivariate logistic regression was used to evaluate public rental housing as an independent risk factor for admission risk, emergency department and specialist outpatient clinic attendances. Results: 14,457 unique patients were analysed and 2,163 patients (15.0%) were rental housing residents. Rental housing patients were significantly more likely to be without a spouse; required financial assistance; have chronic obstructive pulmonary disease; usage of anti-depressant and anti-psychotic medications; longer length of hospital stay during the index admission; and higher Charlson Comorbidity Index scores. After adjusting for demographics and clinical variables, staying in public rental housing remain an independent risk factor for readmission within 15 and 30 days, frequent hospital admissions and Emergency Department attendances in Singapore. Conclusion: Our study showed an association between public rental housing with readmission risk and increased utilization of hospital services in Singapore. A deeper understanding of the residents’ social circumstances and health seeking behaviour would be insightful. Keywords: social determinant of health; readmission, hospital utilization; housing